Sort by

- Relevance
- |Time

...the ODE becomes x^2 y^4 dx + 2x^3 y^3 dy = 0, but this time, the

**LHS**isn't an exact differential, so this expression (x^2 y^3) didn't turn out to be...1 Answers · Science & Mathematics · 03/12/2013

...you can't use Voc is because the calculated value of the

**LHS**assumes R2, but the right hand side replaces R2 with...3 Answers · Science & Mathematics · 07/09/2012

...3n +4n +6 - ( 2n^2 +n +2n +1) = 4n +5 Yes !! We get

**LHS**= RHS in an easily recognisable form !! This holds...3 Answers · Science & Mathematics · 27/05/2010

... the tank contains 900 kg of water, the z = 0.9 m, so the

**LHS**of EQUATION S is 3/7 of 1 second, 3/7 = 5/7 - 0...2 Answers · Science & Mathematics · 14/03/2012

...0 similarly gives B = 2 Because the coefficient of x on the

**LHS**is zero, A + B = 0, and hence A = -2 Hence the...3 Answers · Science & Mathematics · 19/07/2012

...(x_1,x_2)P(x)dx - Int(x_1,x_2)H(x)dx ?= 25

**LHS**= 25 ==> CHECKED1 Answers · Science & Mathematics · 23/07/2011

the right side of the equation looks weird.....okay is looks meaningless. I don't think You can take the partial derivative of an infinitesimal

1 Answers · Science & Mathematics · 01/05/2012

Your answer for the first qquestion is correct. For second question follow the two DeMorgan laws: (A+A)' = A'.A' (A.A)' = A'+A'

2 Answers · Science & Mathematics · 19/05/2007

Your first answer is correct -- quite a few steps though you cold say XX'+YY+XY+X'Y ≟ Y 0 + Y + (X + X')Y ≟ Y and since (X + X') =1 0 + Y + Y ≟ Y...

1 Answers · Science & Mathematics · 19/05/2007

(11-2x)/((x+3)(x+1)) dx = dt. Take a integration!!!

2 Answers · Science & Mathematics · 21/01/2012